Research on DC Reference Voltage Characteristics of Surge Arrester under Low Temperature Conditions in Extremely Cold Regions - Zhang, Kexin; Wang, Lei; Zhang, Peng; Liu, Heqian; Yang, Hongda; Li, Zhongyuan (2022 IEEE 2nd International Conference on Data Science and Computer Application (ICDSCA), 2022)
Metal oxide arresters (MOA) are generally installed outdoors, and the temperature will affect the state parameters of MOA. The existing regulations do not provide quantitative reference conversions for the DC reference voltage and leakage current of MOA operating at low temperatures. The value still needs to be judged by experience in the project. Heilongjiang is located in the northernmost part of China, and the temperature in winter is lower than 0^{°} C , or even lower than -20^{°}C . Therefore, the research on the DC reference voltage characteristics of MOA under low temperature conditions in extremely cold regions can provide guidance for the operation status of arresters at low temperatures, and accurately diagnose the operating status of the arrester.